2001
DOI: 10.1001/archneur.58.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Cognitive Impairment and Dementia in Elderly Persons

Abstract: Regular physical activity could represent an important and potent protective factor for cognitive decline and dementia in elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
807
8
61

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,286 publications
(919 citation statements)
references
References 53 publications
43
807
8
61
Order By: Relevance
“…Similarly, a prospective study also demonstrated that physical activity was protective against the development of cognitive impairment, AD, and any types of dementia, and that the highest activity group showed a 60% decrease in the incidence of AD [8] .…”
Section: Exercise Decreases Risks Of Alzheimer's Disease (Ad)mentioning
confidence: 86%
“…Similarly, a prospective study also demonstrated that physical activity was protective against the development of cognitive impairment, AD, and any types of dementia, and that the highest activity group showed a 60% decrease in the incidence of AD [8] .…”
Section: Exercise Decreases Risks Of Alzheimer's Disease (Ad)mentioning
confidence: 86%
“…Exercise is reported to improve cognitive function, reduce the risk of developing cognitive impairment and reduce neuropathology in humans or in animal models [3,61,69,115]. In aging dogs, behavioral enrichment leads to significant improvements in visual discrimination learning and frontal-dependent reversal learning [80].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in physical activity may thus lower the risk of cognitive decline and dementia by improving cognitive reserve. 13,15,16,18,50,89,90 Higher cognitive reserve may help the subject engage in regular physical activity to cope with the first cognitive symptoms of AD. This effect may delay the onset of the clinical manifestations of the disease, which may become apparent only later.…”
Section: Basic Researchmentioning
confidence: 99%